ODONATA (DRAGONFLIES AND DAMSELFLIES) NAIADS IN SUB HIMALAYAN FOOTHILLS OF PAKISTAN - M. Naeem; S. Sattar; A. Zia; A. Rehman; T. Iqbal; S. A. Mehmood; S. Ahmed; K. Shahjeer (Journal of Animal and Plant Sciences, 2022)
A series of surveys were conducted during two consecutive years (2014-15) to explore the Odonata naiads from the sub-Himalaya of Pakistan and it revealed 23 species. Sub-order Anisoptera was represented by 16 species under 13 genera, and suborder Zygoptera represented 07 species under 05 genera. In Anisoptera, the family Libellulidae, followed by Aeshnidae and Gomphidae, was recorded as dominant. While in Zygoptera, the dominant family was recorded as Coenagrionidae, followed by Chlorocyphidae. For each recorded species, individual diagnosis, details like date of collection, number of male/females recorded, coordinates of locality, prevalent air temperature at localities, water body temperature, global distribution, and habitat description are provided. In Pakistan, taxonomic and faunistic studies on Odonata nymphs are highly limited and thus, it was decided to enhance knowledge over this ignored and neglected group by thoroughly surveying sub-Himalaya in Pakistan, which is less explored for biological surveys, especially for class Insecta. The manuscript brought forward a record of five naiads species for the first time from Pakistan.
Keywords: Naiads; Odonata; Anisoptera; Zygoptera; Sub Himalaya; Pakistan